Bureaucracy for a democracy the struggle of the Philippine political leadership and the civil service in the post-Macros period - Cariño, Ledivina V. (Philippine Journal of Public Administration, 1989)
Transition from authoritarianism to democracy can breed strained relations between the political leadership and its civil service. Each institution faces a dilemma. The political leadership must redemocratize and remove vestiges of authoritarianism in society, including residual influences left in the civil service it inherited from its predecessor-regime. On the other hand, the bureaucracy as both instrument and victim of authoritarianism wishes to be part of the redemocratization of society, but has to labor under the distrust of its past by the new political leadership. Under these conditions, the new government employs various policies, actions and decisions in attempting to redemocratize the bureaucracy. These involve changes in personnel, organization, practices and programs of the civil service. However, the process by which these changes are carried out by the political leadership could invite questions on its avowal for democratic ideals.